Optimal management of sarcomas of the breast: an update. Issue 6 (June 2014) - Nizri, Eran; Merimsky, Ofer; Lahat, Guy
<x xml:space="preserve">Abstract</x> Breast sarcomas are rare mesenchymal-derived breast tumors. The small number of patients, the different histological subtypes, and the variation in clinical practice impairs the ability to draw firm practice recommendations. Patient management is often extrapolated from other soft tissue sarcomas, mostly of the extremities in which more clinical data is available. Surgical resection with negative margins is the goal of treatment, irrespective of the surgical procedure; the implication of radiation and chemotherapy is variable. Further advances in treatment should follow the assembly of breast sarcoma patients in specific cancer networks in specialized sarcoma referral centers. The characterization of molecular pathways active in tumorogenesis of these tumors may pave the way for the application of novel therapeutic agents.